The Impact of Natural Disasters on International Trade: The Potential Effects of April 2024 Dubai Floods on Ghana’s Economy - Israel Kofi Nyarko (Business, Management and Economics: Research Progress Vol. 4, 2024)
This chapter examines the repercussions of the April 2024 Dubai floods on Ghana’s trade and proposes actionable strategies for resilience and growth. It investigates the influence of natural disasters on international trade through a comprehensive literature review, focusing on challenges faced by developing economies like Ghana. The unprecedented weather event disrupted international travel, halted airport operations, and caused widespread transportation chaos. The flooding highlighted the UAE’s vulnerability to extreme weather, particularly its infrastructure. The chapter underscores the interconnectedness of global trade networks and the critical need for proactive risk management. Synthesizing and analyzing qualitative literature from previous studies reveals that over the last three years, Ghana’s exports to the United Arab Emirates have grown significantly, from 117 million in 2021 to 1.71 billion in 2023. This growth suggests enhanced market access, diversified product offerings, and rising demand for Ghanaian goods in the UAE, as well as the potential for further growth. Despite this increase, the UAE’s imports into Ghana have varied over time, resulting in a trade deficit due to a consistent trend of imports exceeding exports. The chapter finds that the Dubai floods can potentially disrupt Ghana’s trade activities and economic growth, underscoring the importance of resilience-building measures and diversification of trade partners and markets. The analysis elucidates the potential impact of Dubai’s floods on Ghana’s trade patterns, economic growth, and long-term development possibilities. It highlights the possible effects that interruptions in global supply chains and trade could have on Ghana’s export-oriented industries, capital accessibility, and overall economic stability. Recommendations include investing in resilient infrastructure, promoting digital trade, enhancing institutional capacity, and fostering regional cooperation. By offering insights for policymakers, businesses, and stakeholders, this chapter contributes to understanding the resilience of developing economies to natural disasters. It provides practical guidance for Ghana to navigate the challenges posed by the Dubai floods and achieve sustainable growth.